PENERAPAN BRONJONG SEBAGAI PERKUATAN TEBING PADA SUNGAI PAPPA - Virlayani, Asnita; Mustakim, Mustakim; Sulfanita, Andi (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
The Pappa River is one of the rivers in South Sulawesi which often experiences flooding during the rainy season. The flooding that occurred resulted in scouring of the river cliffs, so to prevent damage to the cliffs and the expansion of the river, it was necessary to plan cliff supports in the form of gabions. This research aims to determine the form and dimensions of effective slope strengthening planning in the Pappa River, Takalar Regency. Planning the dimensions of retaining walls includes design of gabion size and gabion stability and is analyzed using the gabion reinforcement capacity formula based on SNI 03-0090-1999. The calculated results of the overturning forces were 8.82 ≥ 1.5 and the shearing forces was 4.34 ≥ 1.5 so that the gabion construction was safe. Meanwhile, the gabion building will be placed on a cliff downstream of the Jenelata river, 200 meters long with dimensions 2 x 1 x 0.5, number of partitions 1 and capacity of 1 m³